Protocolos de enxertia do tomateiro combinado com portaenxertos de diferentes cultivares e espécies de solanáceas. - Garcia, Manuel Filipe Nascimento (2015)
The grafting technique has been cited by many researchers as an important tool to be adopted for tomato production in harsh environmental conditions, especially when occur problems related to the soil. Based on the above the main objective of this study was to develop grafting protocols for tomato 'Santa Clara' grafted in different varieties and species of Solanaceae. All developed works were conducted in the randomize design blocks in a factorial scheme (3 x 2) + 1, i.e. three grafting methods (bezel with graffiti grafting, cleft grafting and plain English grafting) combined with two ages of scion and rootstocks depending on the used species, plus the tomato plant 'Santa Clara' ungrafted (control). The following species were studied individually as rootstock for tomato (Solanum lycopersicum) cv. Santa Clara: 1) Cherry Tomato (S. lycopersicum var. cerasiforme) cv. Carolina; 2) Eggplant (S. melongena) cv. Roxa comprida; 3) Jilo (S. gilo) cv. Comprido grande rio; 4) Sweet pepper (Capsicum annuum) cv. Yolo wonder; 5) Cocona (S. sessiliflorum Dunal.); and, 6) Jurubeba (S. jamaicense Mill). Were measured: the length (cm) of scion pre and post-grafted; chlorophyll content "a" and "b" pre- and post-grafted; diameter of the pre-grafted scion (mm); and fixation of grafted individuals by assigning notes. The evaluations of grafted plants on all assays were performed seven days after grafting. Based on the results it was possible to establish a grafting protocol for all evaluated combinations. Rootstocks from Solanum gilo and Solanum sessiliflorum provided vigor to the tomato 'Santa Clara' scion. The cleft grafting technique can be indicated as the most effective for grafting of tomato 'Santa Clara' in the Solanaceae varieties and species studied.